2018
DOI: 10.1016/j.neuro.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Valproate and sodium butyrate attenuate manganese-decreased locomotor activity and astrocytic glutamate transporters expression in mice

Abstract: Manganese (Mn) is an essential trace element, but chronic overexposure to this metal, either environmentally or occupationally may cause manganism, a disease analogous to Parkinson’s disease. Inhibitors of histone deacetylases, such as valproic acid (VPA) and sodium butyrate (NaB) exert neuroprotective effects in various animal models of neurological disorders. Thus, the present study investigated whether VPA or NaB prevent Mn-induced neurotoxicity by assessing locomotor activities and expression of astrocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Other studies found little to no neurotoxicity in mice after single intraperitoneal (IP) doses of manganese chloride at 66 mg/kg (Fontaine et al, 2017), or short-term repeated IP injection in rats reaching final doses of 60 mg/kg (Galosi et al, 2017). To date, many studies have investigated alternative administration paradigms (see next section), alternative manganese-containing compounds (discussed in section “Mangafodipir”) and co-administration of additional compounds (Alahmari et al, 2015; Johnson et al, 2018) to mitigate any potential toxic effects of manganese in MEMRI and still retain useful imaging enhancement.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Other studies found little to no neurotoxicity in mice after single intraperitoneal (IP) doses of manganese chloride at 66 mg/kg (Fontaine et al, 2017), or short-term repeated IP injection in rats reaching final doses of 60 mg/kg (Galosi et al, 2017). To date, many studies have investigated alternative administration paradigms (see next section), alternative manganese-containing compounds (discussed in section “Mangafodipir”) and co-administration of additional compounds (Alahmari et al, 2015; Johnson et al, 2018) to mitigate any potential toxic effects of manganese in MEMRI and still retain useful imaging enhancement.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Its pharmacological effects involve diverse mechanisms that affect the transmission of nerve signals in vitro and in vivo . VPA is neuroprotective in some neurological diseases 2 , 3 . VPA was also found to decrease the excitation of neurons by N-methyl-D-aspartic acid (NMDA), inhibit voltage-gated sodium (Nav) channels, and modify the firing of neuronal cells 4 .…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the effects of NITyr on global ischemia, both the cognitive and noncognitive behaviors of the gerbil were evaluated, for example locomotion, exploration, and anxiety-related behavior (OFT), motor function (RRT) and the ability of learning and memory (MWM). 17,18) NITyr had no effects on the autonomic activity, investigating behavior and anxiety behavior in the OFT, but increased the motor function in the RRT during the extension of the training time, indicating that NITyr could improve the motor function of the gerbil through enhancing the ability of learning and memory, but not affecting motor function. The improvement of learning and memory impairment might be related to the repairmen of damaged brain tissue rather than the improvement of motor ability of the gerbil.…”
Section: Discussionmentioning
confidence: 87%